The Hubungan antara citra tubuh dengan kepercayaan diri pada model di Agency X - Shantiyani, I Gusti Ayu Yurika Wahyuning; ,S.Psi., M.Psi., Psikolog, Ni Made Sintya Noviana Utami; ,S.Psi., M.A., Nyoman Trisna Aryanata (Bali International University, 2023)
Background: A model must be confident to support performance in doing their job. The model's self-confidence is influenced by physical appearance, which is closely related to body image. Body image includes feelings of satisfaction and even dissatisfaction with the body, which can even cause psychological problems. Purpose: This research aims to determine the relationship between body image and self-confidence, the contribution of body image to self-confidence and the image of body image and self-confidence in the Agency X model. Method: This research uses quantitative method with cross-sectional design. The subjects of this research were 40 model people in Agency X who were taken with a simple random sampling technique. This research scale includes a scale of body image and self-confidence adapted from Andiyati (2016) and analyzed using a simple linear regression test. Result: A significance values is 0.000 (α < 0,05) and the R Square value is 0,339. Most of the body image of the study subjects was classified as moderate with a percentage of 57,5% dominated by aspects of appearance orientation. Meanwhile, the self-confidence of most subjects is relatively high with a percentage of 45% dominated by rational and realistic aspects. Conclusion: There is a positive relationship between body image and self-confidence in models at Agency X. Body image has contributed 33,9% to self-confidence. The body image of the model in Agency X is in the medium category, while the confidence of the model in Agency X is in the high category.